(untitled) (Journal of Parents and Teachers, 2025)
The article discusses how a teacher should organize a classroom, not only when teaching but also when organizing activities, taking into account the timing, the different learning paces of the students, the language that should be used, and, of course, the positive, understandable, and non-verbal instructions that need to be developed.